2017
DOI: 10.1002/ejp.1007
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous analgesic effect of pregabalin: A double‐blind and randomized controlled trial

Abstract: Background: Conditioned pain modulation (CPM) is widely used to measure endogenous analgesia, and a recent study indicated that drugs that act on endogenous analgesia are more effective in individuals with lower CPM. Recent animal studies have indicated that pregabalin activates endogenous analgesia by stimulating the descending pain inhibitory system. The present study examined whether the analgesic effect of pregabalin is greater in individuals with lower original endogenous analgesia using CPM. Methods: Fif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Sugimine et al explored the effect of Pregabalin on conditioned pain modulation in a placebo controlled study . There was a clear correlation between baseline conditioned pain modulation and that after receiving Pregabalin ( r = 0.73, P < 0.0001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sugimine et al explored the effect of Pregabalin on conditioned pain modulation in a placebo controlled study . There was a clear correlation between baseline conditioned pain modulation and that after receiving Pregabalin ( r = 0.73, P < 0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests that assessment of conditioned pain modulation may allow for the individualisation of pain treatments in other conditions of chronic pain; for example, Wilder-Smith et al and Landau etal showed that baseline conditioned pain modulation may predict postsurgical neuropathic pain [48][49][50][51][52]. Sugimine et al explored the effect of Pregabalin on conditioned pain modulation in a placebo controlled study 53. There was a clear correlation between baseline conditioned pain modulation and that after receiving Pregabalin (r = 0.73, P < 0.0001).…”
mentioning
confidence: 99%
“…Pregabalin, a GABAergic medication used to treat neuropathic pain and fibromyalgia among other conditions, may also produce its analgesic effect by enhancing CPM. Importantly, pregabalin efficacy is influenced by initial CPM efficacy, such that individuals with less efficient CPM benefit more from the drug (Sugimine, Saito, Araki, Yamamoto, & Obata, 2017). …”
Section: A Few Other Pharmacological and Therapeutic Applicationsmentioning
confidence: 99%
“…The latest guidelines for acute burn pain from the American Burn Association in 2020 suggest the adjunctive use of gabapentinoids for refractory burn pain and neuropathic pain, based on only two RCTs and three non-RCTs [2]. To provide updated and evidence-based recommendations, we included five RCTs in our systematic review and excluded studies if burn pain was elicited by experimental models, such as thermodes or intradermal capsaicin [24,25]. All of the included trials on the adult population applied baseline analgesics using morphine with or without other adjunctive medication.…”
Section: Discussionmentioning
confidence: 99%